THE THEMEDA QUADRIVALVIS TALL-GRASS SAVANNAH OF OMAN AT THE CROSSROAD BETWEEN AFRICA AND ASIA - Patzelt, A. (Edinburgh Journal of Botany, 2011)
Vegetation analysis reveals that the Themeda quadrivalvis tall-grass savannah in Oman, southern Arabia, forms a clearly defined belt with strong edaphic and geomorphological characteristics. The newly described association Desmodio gangetico-Themedetum quadrivalvis ass. nov. is interpreted as an impoverished easternmost outlier of the East African savannah.